p2-33p+16=0

Simple and best practice solution for p2-33p+16=0 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for p2-33p+16=0 equation:



p2-33p+16=0
We add all the numbers together, and all the variables
p^2-33p+16=0
a = 1; b = -33; c = +16;
Δ = b2-4ac
Δ = -332-4·1·16
Δ = 1025
The delta value is higher than zero, so the equation has two solutions
We use following formulas to calculate our solutions:
$p_{1}=\frac{-b-\sqrt{\Delta}}{2a}$
$p_{2}=\frac{-b+\sqrt{\Delta}}{2a}$

The end solution:
$\sqrt{\Delta}=\sqrt{1025}=\sqrt{25*41}=\sqrt{25}*\sqrt{41}=5\sqrt{41}$
$p_{1}=\frac{-b-\sqrt{\Delta}}{2a}=\frac{-(-33)-5\sqrt{41}}{2*1}=\frac{33-5\sqrt{41}}{2} $
$p_{2}=\frac{-b+\sqrt{\Delta}}{2a}=\frac{-(-33)+5\sqrt{41}}{2*1}=\frac{33+5\sqrt{41}}{2} $

See similar equations:

| n+(n+40)+(n-30)=150 | | 2m/5+7/10=9/2 | | 6(y+7.7)-8y=-9 | | x*x*x+2x=26 | | 2x+1=7,x= | | -2x+7x=x | | 9(c+9.6)+6=5.2c+1.5 | | 9x-5(2x-9)=2(x-1)+9 | | 2(y+7)=5y-1 | | (3x)(-5x)=-2x | | 6x+(2x*2(2x*2-1)+(3x*2-1+2x)-2x+1)+2x-1=3 | | 0=4.6(t+9.5) | | 3994x+2x+(7x+(2x-1)+3x-1)=17 | | 5+6y^2+7y=8 | | 9a-5-3a=13 | | ((3x+2x)*2+2x-1)+(2x+3-x)+2x-1=5x+x+(2-3x)-1 | | 3+2x+2=5 | | (3x*2+1(2x+2))^2=1 | | (2x+3x)x+(5x-2+2x)x=x-3x(2x+1)-2 | | (2*2)x+(3*2)x+2x+x=2x+3-2+1x | | 15·y=75 | | 5x+x+2x+3x=2x-1+(3x*2)*2 | | 17/18=x/27 | | 3x+2x+x+2x=-x+x+2 | | 9w^2+8w=0 | | 2a^2-8a=-6 | | 2+x+x+x+2=5 | | (x+1)^3=11 | | 6+x+(2*x-1)^2=3 | | 7k+2=4 | | 5x+2x+x=3*2 | | 4+x+x+x=3 |

Equations solver categories